Efficacy, Safety and tolerability of the once-daily 10 cm² rivastigmine patch formulation in the patients with dementia (with probable Alzheimer’s disease) (Bangladesh Journal of Neuroscience, 2013)
Back ground: Treatment compliance in patients with Alzheimer’s disease is particularly important as patients receiving regular treatment have a greater chance of slowing or delaying disease progression. Transdermal delivery has the potential for providing continuous drug delivery and steady plasma levels. Current study aimed to evaluate safety and tolerability of rivastigmine patch, to assess patient compliance and to assess the efficacy of treatment in patients with dementia (with probable Alzheimer’s disease).Methods: A total of 112 dementia patients (with a diagnosis of probable Alzheimer’s disease) from 12 centers were enrolled who were residing with someone in the communities throughout the study. After eligibility, and baseline assessments, patients were entered a 24-week open label treatment phase. All patients were started with application of one 5 cm² patch, followed by an up-titration to the target dose of 10 cm² patch size. Efficacy assessments were performed at weeks 12 and 24 in terms of MMSE and GDS score. Safety was monitored at all assessment points based mainly on the frequency of adverse events.Results: Analysis of baseline and available data until the drop out revealed no significant differentials. Around 95% of the study participants could receive 10 cm² patch size, showing a very high tolerability of the patch. Concurrent medication use also showed significant reduction to 16.3% patient in the end from 25% at baseline. The average MMSE score increased to 19.3 (±3.1) at 12th week and to 20.6(±3.4) at 24th week from 16.8 (±3.2) at baseline. GDS score reduced to 3.7 (±1.4) at 12th week and to 3.2 (±1.3) at 24th week from 4.3 (±1.5) at baseline. Only eight occasions of adverse event was reported (8.2%); no serious adverse event (SAE) were reported. Lost to follow up in the study was 14 (12.5%). Analysis of baseline data shows no significant difference. Their withdrawal seems to be unrelated to the adverse events and treatment outcome. Among the lost to follow up only one 1 (7.1%) had some side effect.Conclusion: Our study supports the pharmacokinetic rationale for the rivastigmine patch, indicating that smooth and continuous delivery of rivastigmine translates into an improved tolerability profile versus conventional oral administration, while maintaining clinical effectiveness.Bangladesh Journal of Neuroscience 2013; Vol. 29 (1) : 5-14